Study on the association between pregnancy-associated plasma protein-A and acute cerebral infarction - Zheng, Sihang; Hossain, Mohammad Showkat; Wu, Hongliang; Nao, Jianfei (Frontiers in Neurology, 2023)
Objective: To study the correlation between pregnancy-associated plasma protein-A (PAPP-A) and acute cerebral infarction (ACI).Methods: Patients who had the symptoms of paralysis, aphasia or sudden neurological impairment from June 2020 to October 2021 were chosen. There were 159 patients diagnosed with ACI as the experimental group and 102 patients without ACI as the control group. Collect clinical datas and observe whether them have a certain impact on plasma PAPP-A levels. The ACI group was divided into two groups as mild neurological deficit group (NIHSS score <3) and moderate and severe neurological deficit group (NIHSS score >3). The ACI group were divided into the atherosclerotic type group and the arteriolar occlusion type group according to TOAST classification. The ACI group were divided into good prognosis group (mRS ≤ 2 points) and poor prognosis group (mRS>2 points) using the Modified Rankin Scale (mRS) for 90 days of follow-up. Plasma PAPP-A levels were compared between those groups.Results: 1. The plasma PAPP-A level in patients with ACI (1.840±0.281) was significantly higher than that in the control group (1.690±0.260). Smoking history, leukocyte count, cystatin C, homocysteine and plasma PAPP-A levels were independently correlated with ACI. 2. The level of PAPP-A in patients with moderate and severe neurological impairment was lower than that in patients with mild neurological impairment. 3. The level of PAPP-A in patients with arteriolar occlusion type group was higher than that in patients with atherosclerosis type group. 4. The PAPP-A This is a provisional file, not the final typeset article 2 levels in the group with elevated low-density lipoprotein are higher than those in the group with normal low-density lipoprotein. 5. Plasma PAPP-A level was not correlated with infarction location, infarction volume, or prognosis at 90 day follow-up.Conclusion: 1. The level of plasma PAPP-A could be the independent risk factor of ACI. It is positively correlated with triglyceride and cholesterol content. 2. PAPP-A level is positively correlated with low-density lipoprotein. 3. PAPP-A levels between different disease severity have significant difference. 4. The level of plasma PAPP-A in the arteriolar occlusion type group was higher than that in the atherosclerotic type group.